2001
DOI: 10.1046/j.1472-765x.2001.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable alpha-amylase production by an extreme thermophile Bacillus thermooleovorans

Abstract: Bacillus thermooleovorans produces a calcium-independent and thermostable amylase which can find use in starch saccharification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 9 publications
(8 reference statements)
4
20
0
Order By: Relevance
“…The amylase yield is highest in presence of maltose and soluble starch (1260 ± 8.2 U/g and 1230 ± 24.6 U/g) respectively compared to fermented WB (1170 ± 16.5 U/g). This is in agreement with the observation reported in case of Bacillus thermoleovorans preferring starch, glucose, lactose, maltose and maltodextrin as carbon sources for amylase production [31]. Wealth of information is also available in this context regarding improved yield of amylase from Bacillus licheniformis, Bacillus species I3 and Bacillus Stearothermophilus in presence of starch in the fermentation media [10,34].…”
Section: Effect Of Sugar Additives On the Amylase Yield From Bacillussupporting
confidence: 90%
See 1 more Smart Citation
“…The amylase yield is highest in presence of maltose and soluble starch (1260 ± 8.2 U/g and 1230 ± 24.6 U/g) respectively compared to fermented WB (1170 ± 16.5 U/g). This is in agreement with the observation reported in case of Bacillus thermoleovorans preferring starch, glucose, lactose, maltose and maltodextrin as carbon sources for amylase production [31]. Wealth of information is also available in this context regarding improved yield of amylase from Bacillus licheniformis, Bacillus species I3 and Bacillus Stearothermophilus in presence of starch in the fermentation media [10,34].…”
Section: Effect Of Sugar Additives On the Amylase Yield From Bacillussupporting
confidence: 90%
“…Alpha amylase yield has been augmented from solid state fermented production media with proper supplementation of C and N sources as they are absolutely necessary for microbial growth [29,30]. From earlier literature it is known that the presence of (NH 4 ) 2 SO 4 , NH 4 Cl and NH 4 HPO 4 in SSF media along with WB stimulates enzyme production [31]. However in our studies, highest amylase yield has been observed in presence of 0.125M NH 4 NO 3 (1410 ± 16.9 U/g) compared to the others ( Figure 5).…”
Section: Effect Of Extraction Solvent and Nitrogen Sources On The Amymentioning
confidence: 99%
“…Source and Maintenance of Strain G. thermoleovorans NP 54 was isolated from a water sample collected from the hot water spring of the Waimangu volcanic valley (New Zealand) and maintained as described earlier [26][27][28][29][30]. The culture is deposited at Microbial Type Culture Collection, Institute of Microbial Technology, Chandigarh (India; MTCC 4220).…”
Section: Methodsmentioning
confidence: 99%
“…Immobilization matrices and conditions must be selected for each microbial strain [24]. We have been publishing several research papers on production, purification, and characterization of α-amylase from G. thermoleovorans [25][26][27][28][29][30][31]. However, there is still a need to develop a sustainable enzyme titer and continuous culture of G. thermoleovorans by using immobilization, aerobic, and anaerobic fermentation processes; for that, the present investigation was undertaken to understand the nature of synthesis of Ca 2+ -independent, high maltose-forming, and hyperthermostable α-amylase in free as well as immobilized cells of G. thermoleovorans in aerobic and anaerobic fermentation.…”
mentioning
confidence: 99%
“…when grown in a fermenter (Priest 1977). A two-fold increase in the b-xylosidase titre was attained Microbiol Biotechnol (2007) 23:483-490 487 in 30-36 h in Thermomyces lanuginosus MH4 (Illias and Hoq 1998) and Bacillus thermoleovorans (Narang and Satyanarayana 2001). This can be attributed to the improved process parameters in the fermenter (Humphrey 1998).…”
Section: Xylanase Production (Ulmentioning
confidence: 99%